Curriculum Issues in Indonesia: Teacher’ Implementation and Students’ Perception Toward K13 In ELT - Isumarni, Isumarni; Hermansyah, Sam; Faradillah, Nurul; Hikmah, Nur (Journal International of Lingua and Technology, 2023)
One of the most controversial curriculums implemented in Indonesia is 2013 curriculum. After the government assigned that in 2023 all of schools are expected to use the 2013 curriculum, yet in December 2014 the Ministry of Education changed the obligation with stated that the school that implemented the 2013 curriculum for about one semester should go back to KTSP curriculum. Frequently curriculum change in Indonesia give impact for teaching and learning process and to education stockholder. This study aimed to investigate the implementation of the 2013 curriculum in English teaching practice, to know the problems that teacher and student faces in the implementation of the 2013 Curriculum in ELT practice, and also to analysis the students’ perception toward ELT practice related to the implementation of the 2013 curriculum. Descriptive qualitative research is the design of this research. Subjects of this research are English teacher and student of one vocational school in Indonesia. The data were collected by using triangulation method namely interview, observation and documentation. Semi-structured interview used to get the data about the English teacher’s understanding toward the implementation of the 2013. Classroom observation use to observed the English teacher’s teaching practice in implementing the 2013 curriculum. The researcher also interviewed students to know the students’ perception toward the ELT practices and the problems face by students in ELT practice. The data from interview and were analyzed through interactive model analysis develop by Miles and Huberman (1994). Findings showed that the teacher’s understanding toward the aspects in teaching process of Standard Process of the 2013 Curriculum was satisfactory. In the main activities, teacher’s teaching practice is accordance with the teaching process of the standard process of the 2013 curriculum. The limited time allotted for English subject was the main problems in teaching English by implementing the 2013 curriculum. The students’ perception toward the ELT process in their class was positive because all of them stated that the English class was enjoyable. The most problem that the students found in learning English is speaking. Based on the students’ interview, the researcher assumed, the limited time to practice English cause the difficulty in speaking.